Incidence of Traumatic Brain Injury in the U.S. Military, 2010–2014. Issue 5 (4th December 2018) - Agimi, Yll; Regasa, Lemma Ebssa; Stout, Katharine C
Abstract: Introduction: Traumatic brain injury (TBI) is a significant health issue that affects U.S. military service members (SM) at home and in combat deployments. We estimated the TBI incidence rate in the deployed and non-deployed setting between 2010 and 2014 and identified subgroups with elevated rates for prevention efforts. Methods: Retrospective population-based study of all active duty U.S. military SM that sustained a first active duty TBI diagnosis between January 2010 and December 2014 collected and analyzed in 2017. Using Armed Forces Health Surveillance Branch data we calculated the Mantel–Haenszel (MH) standardized TBI incidence rate in the deployed and non-deployed setting, adjusting for service and demographic factors. Results: From 2010 to 2014, the MH standardized incidence rate for deployed SMs was 3, 265 TBIs per 100 thousand p-yrs (95% CI: 3, 222–3, 307) and 1, 705.2 (95% CI: 1, 694.0–1, 716.5) for non-deployed SMs. The youngest deployed male Army soldiers, those ages 17–24, especially White and Hispanic soldiers, had the highest TBI incidence rate (IR) of 5, 748.7 (95% CI: 5, 585.8–5, 916.4) and 5, 010.3 (95% CI: 4, 647.5–5, 401.4), respectively. The IR for all branches was 1, 972.6 (95% CI: 1, 959.5–1, 985.7) and 724.0 (95% CI: 714.9–733.0) for Reserve/Guard Service members. Conclusions: Across all years, Marines and Army Soldiers experience the highest rates of injury with deployed SMs having elevated IRs of TBI. The TBI IR among deployed SMs was 91% higher than among those in the non-deployed setting, due to continued exposures to combat. Deployed Reserve/Guard component SMs seem to have an above average rate, a finding with implications for training and prevention.